2019
DOI: 10.5799/jmid.614241
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Inducible Clindamycin Resistance among Staphylococcus aureus Skin and Soft Tissue Infections in A Tertiary Care Hospital

Abstract: Objectives: Drug resistant phenotypes like MRSA are difficult to treat requiring higher group of antibiotics. Topical agents like clindamycin can be used for the therapy of MRSA. The knowledge of prevalence of inducible clindamycin resistance phenotype is essential to prevent treatment failure. Methods:A total of 204 staphylococcal isolates obtained from skin and soft tissue infections and MRSA was detected by Cefoxitin disc diffusion method and detection of Mec A gene by Polymerase chain reaction (PCR). Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Studies across India have reported prevalence of MRSA to be ranging from 7.5% to as high as 90.77% in isolates from SSTIs. [21][22][23][27][28][29] MRSA infections are difficult to treat, as some strains produce biofilms. [30] In fact, few studies have found the prevalence of biofilm-producing MRSA to be as high as 78.8%.…”
Section: Discussion Statement 1: Prevalence Of Sstis In India Range From 17% To 25%mentioning
confidence: 99%
“…Studies across India have reported prevalence of MRSA to be ranging from 7.5% to as high as 90.77% in isolates from SSTIs. [21][22][23][27][28][29] MRSA infections are difficult to treat, as some strains produce biofilms. [30] In fact, few studies have found the prevalence of biofilm-producing MRSA to be as high as 78.8%.…”
Section: Discussion Statement 1: Prevalence Of Sstis In India Range From 17% To 25%mentioning
confidence: 99%